2020
DOI: 10.1002/adfm.201910676
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Combinational Radio–Immuno Oncotherapy

Abstract: Radiotherapy, a clinically used local treatment modality of cancers, is regarded as a promising candidate to promote current immunotherapy through initiating an in situ vaccination effect and reprogramming the immunosuppressive microenvironment. The combination of radiotherapy and immunotherapy, referred to as combinational radio–immuno oncotherapy (CRIOT), elicits a synergistic antitumor effect based on the immunomodulatory properties of radiation. Unfortunately, current CRIOT accompanies low response rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 153 publications
1
48
0
Order By: Relevance
“…The efficient accumulation of AIE NPs at the tumour site is mainly due to the enhanced permeability and retention (EPR) effect. [55][56][57] The results show that the bright NIR NPs obtained through rational molecular design hold great promise for precise non-invasive tumour diagnosis in a high contrast manner.…”
Section: Resultsmentioning
confidence: 99%
“…The efficient accumulation of AIE NPs at the tumour site is mainly due to the enhanced permeability and retention (EPR) effect. [55][56][57] The results show that the bright NIR NPs obtained through rational molecular design hold great promise for precise non-invasive tumour diagnosis in a high contrast manner.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with viral vectors, non-viral vectors are safer and more desirable. Therefore, the development of safe non-viral vectors is highly desirable (97,149,152,153).…”
Section: Aptamer-based Hydrogels For Multifunctional Gene and Cancer mentioning
confidence: 99%
“…A large and growing body of studies have demonstrated the synergistic effects of biomaterials combined with cancer immunotherapy direct the path to address these limitations (Guo et al, 2020;Sang et al, 2019;Zhang et al, 2020). Lately, a variety of biomaterials, such as nanoparticles, implantable biomaterial scaffolds and injectable biomaterial scaffolds, have been introduced to promote immune response and improve the anti-tumor effect (Feng et al, 2020;Li et al, 2019;Wang et al, 2020;Xie et al, 2018). Improved delivery technologies using these materials can induce systemic immune therapeutic responses, while avoiding systemic toxicity (Chen et al, 2019;Ding et al, 2019c;Qiu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%